Meningkatkan Hasil Belajar Pakat Melalui Model PBL Fase B Kelas IV Di SDN Karangasem 2 Surakarta - Achilia Sasanty Wijayanti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to improve the learning outcomes of Catholic Religious Education (PAKAT) through the implementation of the Problem Based Learning (PBL) model in Phase B of Grade IV at SD Negeri Karangasem 2 Surakarta. This Classroom Action Research (CAR) was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observation, learning outcome tests, and documentation. The results show a significant improvement in both cognitive and affective learning outcomes of students. The average cognitive score increased from 86 in the first cycle to 93 in the second cycle, with a 17% improvement. Meanwhile, the affective learning outcomes in the dimension of cooperation also showed an increase from 63% in the first cycle to 74% in the second cycle, with an 11% improvement. In conclusion, the implementation of the PBL model can enhance both cognitive and affective learning outcomes of students in PAKAT subjects at SD Negeri Karangasem 2 Surakarta.